1999
DOI: 10.1128/aem.65.2.431-437.1999
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Starch–Poly(β-Hydroxybutyrate-Co-β-Hydroxyvalerate) Bioplastic in Tropical Coastal Waters

Abstract: Extruded bioplastic was prepared from cornstarch or poly(β-hydroxybutyrate-co-β-hydroxyvalerate) (PHBV) or blends of cornstarch and PHBV. The blended formulations contained 30 or 50% starch in the presence or absence of polyethylene oxide (PEO), which enhances adherence of starch granules to PHBV. Degradation of these formulations was monitored for 1 year at four stations in coastal water southwest of Puerto Rico. Two stations were within a mangrove stand. The other two were offshore; one of these stations was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 23 publications
5
49
0
3
Order By: Relevance
“…An increase of bacterial population correlated with the signs of disintegration of mechanical properties of natural polymer (nP) films, indicating the role of biotic component in degradation process (Orhan et al 2004). Our findings are also similar to the observations of Imam et al (1999) who investigated the degradation of starch-poly (b-hydroxybutyrate-Co-bhydroxyvalerate) bioplastic in tropical coastal waters. They observed that significant biodegradation occurred only after colonization of the plastic, a parameter that was dependent on the resident microbial populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An increase of bacterial population correlated with the signs of disintegration of mechanical properties of natural polymer (nP) films, indicating the role of biotic component in degradation process (Orhan et al 2004). Our findings are also similar to the observations of Imam et al (1999) who investigated the degradation of starch-poly (b-hydroxybutyrate-Co-bhydroxyvalerate) bioplastic in tropical coastal waters. They observed that significant biodegradation occurred only after colonization of the plastic, a parameter that was dependent on the resident microbial populations.…”
Section: Discussionsupporting
confidence: 91%
“…He isolated several bacteria capable of degrading polycaprolactone (PCL) from soil and activated sludge. Imam et al (1999) investigated the degradation of starch-poly (b-hydroxybutyrate-Cob-hydroxyvalerate) bioplastic in tropical coastal waters. They reported that significant biodegradation occurred only after colonization of the plastic, a parameter that was dependent on the resident microbial populations.…”
mentioning
confidence: 99%
“…Starch is an attractive, low-cost filler for biodegradable polymers (Ramsay et al 1993;Imam et al 1995Imam et al , 1998Imam et al , 1999Kotnis et al 1995;Shogren 1995;Willett et al 1998b). When used in its native granular form, starch content in composite materials is usually limited by the loss of mechanical properties (compared with the unfilled polymer) to volume fractions ≤0.30.…”
mentioning
confidence: 99%
“…[2] The tensile properties of poly(3-hydroxybutyrate-cohydroxyvalerate)/polyethylene oxide ((PHBV)/PEO) modified starch blend were decreased after 150 testing days in seawater (Puerto Rico). [3] It can be seen the development of fungi on the surface of starch and blend samples.…”
Section: Introductionmentioning
confidence: 99%